Zero-Sum Game: Geopolitics of Iran’s Aras Valley - Akdemir, İlhan Oğuz; Khakıkhoeı, Jila (Van Yüzüncü Yıl Üniversitesi, 2024)
The Aras is a border and transboundary river. The Aras Valley has strategic importance for various countries in the region as it functions as a transit route and natural border between countries such as Armenia, Azerbaijan, Turkey and Iran. The valley has different geopolitical meanings for regional and global actors. For Armenia, it is important for economic and energy connections as well as access to Azerbaijan's logistics and energy resources. For Turkey, it is valuable as a trade, transportation corridor and access to Central Asia. While it has the potential to provide access to Central Asia in terms of China's "One Belt One Road" project, it has strategic importance in terms of the US's West Asia and Central Asia policies and access to the Caspian energy and control of trade routes. For Russia, it is strategic in terms of remote control of the South Caucasus and establishing contacts with Iran in the region. The Aras Valley is a critical region for Iran in terms of economic, commercial and security. Transportation routes for energy resources in the valley affect Iran's economy and regional security. Access to energy resources, expansion of trade and infrastructure projects can support Iran's economic development. Transportation and commercial activities to be carried out through the Aras Valley can increase Iran’s potential to become a regional power by facilitating its access to Central Asia and even China. Cooperation and dialogue can serve Iran’s interests by strengthening regional stability and security. The aim of this study is to determine the potential benefits of the Aras Valley for Iran. It is aimed to evaluate the potential in the valley in the best way by emphasizing its strategic importance and to examine the economic, commercial and security factors in the region. The study examines the threats that the Islamic Republic of Iran faces in the Aras Valley and what Iran’s strategies should be to prevent them. In addition, geopolitical suggestions regarding the Aras Valley have been made for Iran. There is ethnic and political border incompatibility in the Aras Valley. The study, based on reflectivist theory and progressive method, examines the potential power of the Aras Valley for Iran's geopolitical interests and the policies that Iran should produce on the valley, considering the geographical distribution and historical connections of the ethnic groups in the region.

Aras, sınır teşkil eden ve sınıraşan bir nehirdir. Aras Vadisi, Ermenistan, Azerbaycan, Türkiye ve İran gibi ülkeler arasında geçiş yolu ve doğal sınır olarak işlev görmesi nedeni ile bölgedeki çeşitli ülkeler için stratejik bir öneme sahiptir. Vadi bölgesel ve küresel aktörler için farklı jeopolitik anlamlar ifade etmektedir. Ermenistan için ekonomik ve enerji bağlantılarının yanı sıra Azerbaycan'ın lojistik ve enerji kaynaklarına erişimi önemlidir. Türkiye için ticaret, ulaşım Dehlizi ve Orta Asya’ya erişim olarak değerlidir. Çin'in "Kuşak-Yol" projesi açısından Orta Asya'ya erişim sağlama potansiyeli taşırken, ABD'nin Batı Asya ve Orta Asya politikaları ev Hazar enerjisine erişim ve ticari yolları kontrol bağlamında stratejik öneme sahiptir. Rusya için Güney Kafkasya’yı uzaktan kontrol ve bölgede İran ile irtibat kurma açısından stratejiktir. Aras Vadisi, İran için ekonomik, ticari ve güvenlik açılarından kritik bir bölgedir. Vadideki enerji kaynaklarının ulaşım yolları, İran'ın ekonomisini ve bölgesel güvenliğini etkilemektedir. Enerji kaynaklarına erişim, ticaretin genişlemesi ve altyapı projeleri İran'ın ekonomik kalkınmasını destekleyebilir. Aras Vadisi üzerinden gerçekleştirilecek ulaşım ve ticari faaliyetleri, İran'ın Orta Asya ve hatta Çin'e ulaşımını kolaylaştırarak bölgesel güç olma potansiyelini artırabilir. İş birliği ve diyaloglar, bölgesel istikrarı ve güvenliği güçlendirerek İran'ın çıkarlarına hizmet edebilir. Bu çalışmanın amacı, Aras Vadisi'nin İran için potansiyel faydalarını belirlemektir. Stratejik önemi vurgulanarak vadideki potansiyelin en iyi şekilde değerlendirilmesi ve bölgedeki ekonomik, ticari ve güvenlik faktörlerinin incelenmesi amaçlanmaktadır. Çalışma; İran İslam Cumhuriyeti'nin Aras Vadisinde karşılaştığı tehditlerin neler olduğu ve İran'ın bunları engelleme stratejilerinin neler olması gerektiğini irdelemektedir. Ayrıca İran için Aras Vadisi’ne dair jeopolitik önerilerde bulunulmuştur. Aras Vadisi’nde etnik ve siyasi sınır uyumsuzluğu söz konusudur. Reflektivist teori ve progresif yöntemden yola çıkan çalışma; bölgedeki etnik grupların coğrafi dağılımını ve tarihi bağlantılarını göz önünde bulundurarak İran’ın jeopolitik çıkarları için Aras Vadisi’nin potansiyel gücünü ve İran’ın vadi üzerine üretmesi gereken politikaları ele alacaktır.
Sıfır Toplamlı Oyun: İran’ın Aras Vadisi Jeopolitikaları
Keywords: Political Geography; Siyasi Coğrafya